O uso de substâncias antioxidantes no tratamento de neuropatia periférica induzida por quimioterapia em modelos experimentais - Carvalho, Larissa Feitosa (2017)
Chemotherapy-Induced Peripheral Neuropathy (NPIQ) is characterized by the toxic action of some medications used to treat cancer on the peripheral nerves. Approximately 48% of patients treated with multiple agents have some degree of NPIQ and the main symptoms involve: weakening or sensory loss, numbness, tingling, temperature sensitivity, allodynia, and hyperalgesia in a ‘stocking and glove’ format distribution. There is no definition of a pharmacological approach specific to NPIQ capable of showing relevant clinical benefit. However, in recent years a number of possible neuroprotective drugs have been investigated as an alternative for prevention or treatment of NPIQ. In this context, there are the antioxidant substances that have been used for centuries in preventive medicine and epidemiological studies support the idea that there is an inverse relationship between the levels of antioxidants in an organism and the development of neurodegenerative diseases. Different strategies to prevent and / or treat NPIQ have been developed in pre-clinical models with animals. However, when analyzing the methodologies used in this type of study, some methodological weaknesses arise and it becomes evident the need for a greater interaction between the methodologies developed for the experimental studies and the clinical studies. Thus, the objective of our study was to review the literature on the use of antioxidant substances for the treatment of peripheral neuropathy induced by chemotherapy in experimental models. A search of the SCOPUS, PUBMED and SCIENCE DIRECT databases was carried out in February and March 2016, which covered the works published since 2006. 25 articles were used to prepare the final version of the review.